2010
DOI: 10.1002/ab.20349
|View full text |Cite
|
Sign up to set email alerts
|

Relational aggression in marriage

Abstract: Drawing from developmental theories of relational aggression, this article reports on a study designed to identify if spouses use relationally aggressive tactics when dealing with conflict in their marriage and the association of these behaviors with marital outcomes. Using a sample of 336 married couples (672 spouses), results revealed that the majority of couples reported that relationally aggressive behaviors, such as social sabotage and love withdrawal, were a part of their marital dynamics, at least to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 56 publications
3
58
0
Order By: Relevance
“…Linder et al [2002] found that men and women in emerging adulthood reported equal levels of engagement in romantic relational aggression. With a sample of families with at least one adolescent, Carroll et al [2010] assessed facets of relational aggression in marital conflict (i.e. social sabotage and love withdrawal) and found it to be associated with lower levels of marital quality and greater marital instability for both husbands and wives.…”
Section: Introductionmentioning
confidence: 99%
“…Linder et al [2002] found that men and women in emerging adulthood reported equal levels of engagement in romantic relational aggression. With a sample of families with at least one adolescent, Carroll et al [2010] assessed facets of relational aggression in marital conflict (i.e. social sabotage and love withdrawal) and found it to be associated with lower levels of marital quality and greater marital instability for both husbands and wives.…”
Section: Introductionmentioning
confidence: 99%
“…The experiences that they reported: gossip, exclusion, the silent treatment, negative non-verbal gestures and withdrawal of friendship were similar to experiences found both within children and adolescent samples (Crick & Grotpeter, 1995;Ostrov et al, 2008;Simmons, 2011), as well as findings of prior studies examining the relational aggressive experiences of college students (Gomes et al, 2009;Loudin et al, 2003;Werner & Crick, 1999). The relationships in which these experiences occurred supported prior research indicating college students experience relational aggression with friends (Goldstein, 2011;Werner & Crick, 1999), romantic partners (Carroll et al, 2010;Goldstein, Young, & Boyd, 2007), and in academic settings (Chapell et al, 2004;Dellasega, 2005;Kolanko et al, 2005). These similarities were not unexpected, as prior work had indicated that adult women might continue using relationally aggressive behaviors in adulthood, due both to their effectiveness and a prior history of using relationally aggressive behaviors without consequence (Banny et al, 2011;Beauboeuf-Lafontant, 2009;Dellasega, 2005).…”
Section: Chapter 5: Discussionsupporting
confidence: 75%
“…Studies have found relationally aggressive behaviors in the workplace (Dellasega, 2005), intimate relationships (Carroll et al, 2010;Goldstein, 2011), higher education (Chapell et al, 2004;Dellasega, 2005;Kolanko et al, 2005), and assisted living communities (Trompetter, Scholte, & Westerhof, 2011). One theory is that while the frequency of behaviors may decrease, the behaviors themselves become more complex, secretive, successful, and more difficult to measure quantitatively (Dellasega, 2005).…”
Section: Relational Aggression In Adolescence and Young Adulthoodmentioning
confidence: 99%
See 2 more Smart Citations